Impacts of Land Certification on Tenure Security, Investment, and Land Markets : Evidence from Ethiopia - Deininger, Klaus; Ali, Daniel Ayalew; Alemu, Tekie (World Bank, Washington, DC, 2012)
Although early attempts at land titling in Africa were often unsuccessful, the need to secure rights in view of increased demand for land, options for registration of a continuum of individual or communal rights under new laws, and the scope for reducing costs by combining information technology with participatory methods have led to renewed interest. This paper uses a difference-in-difference approach to assess economic impacts of a low-cost registration program in Ethiopia that, over 5 years, covered some 20 million parcels. Despite policy constraints, the program increased tenure security, land-related investment, and rental market participation and yielded benefits significantly above the cost of implementation.